Response characteristics and efficiency of variable rate fertilization based on spectral reflectance - Chen, Man; Yang, Zhenjie; Wang, Xiaochan; Shi, Yinyan; Zhang, Yu (International Journal of Agricultural and Biological Engineering, 2018)
The key technical problem of variable rate fertilization system based on spectrum information was precise variable fertilization in certain area according to the acquired spectrum information. Hysteretic fertilizing is a critical problem in most of current fertilizer equipment. Hysteresis model was built and analyzed in this study to improve the system. Fertilizing tests were conducted on different wheat breeds and the results were analyzed. The tests showed that variable rate fertilization had obvious hysteresis phenomenon with the maximum lag distance of 3.82 m, the minimum lag distance of 1.73 m and average of 3.06 m. Hysteresis phenomenon of the variable rate fertilization system was obviously decreased when implanting a correction time of 2.04 s with the maximum lag distance of 0.61 m. Variable effects varied by different wheat breeds. Variable rate fertilization had an advantage of improving spatial differences of Yangmai-23, and the spatial variability of which decreased by 14.23%. In the small test area, the amount of fertilizer in Zhenmai-168 decreased by 2.84 kg, while the amount of which in Yangmai-23 increased by 3.83 kg. Yield of Zhenmai-168 in small area was lower than that in traditional pattern, but the condition of Yangmai-23 was on the contrary. Valuable information for increasing performance of fertilization in variable rate fertilization system was provided in this paper.Keywords: variable rate fertilization, fertilization lag, calibration, fertilization efficiency, winter wheatDOI: 10.25165/j.ijabe.20181106.4086Citation: Chen M, Yang Z J, Wang X C, Shi Y Y, Zhang Y. Response characteristics and efficiency of variable rate fertilization based on spectral reflectance. Int J Agric & Biol Eng, 2018; 11(6): 152–158.